C- and O-glycosyl flavonoids in Sanguinello and Tarocco blood orange (Citrus sinensis (L.) Osbeck) juice: Identification and influence on antioxidant properties and acetylcholinesterase activity. (1st April 2016) - Barreca, Davide; Gattuso, Giuseppe; Laganà, Giuseppina; Leuzzi, Ugo; Bellocco, Ersilia
Highlights: Twelve flavonoids were identified/quantified in Sanguinello and Tarocco blood orange. Flavonoids strongly influence the antioxidant activity of Sanguinello and Tarocco. Sanguinello and Tarocco juices display remarkable acetylcholinesterase inhibition. Abstract: Sanguinello and Tarocco are the blood orange ( Citrus sinensis (L.) Osbeck) cultivars most diffused worldwide. Reversed phase liquid chromatography coupled with MS-MS analysis showed that these two varieties have a similar chromatographic pattern, characterised by the presence of C - and O -glycosyl flavonoids. Of the two, Sanguinello was found to be far richer in flavonoids than Tarocco. In the juices, twelve individual components were identified for the first time, namely, four C -glycosyl flavones (lucenin-2, vicenin-2, stellarin-2, lucenin-2 4′-methyl ether and scoparin), three flavonol derivatives (quercetin-3- O -(2-rhamnosyl)-rutinoside, quercetin-3- O -hexoside, quercetin 3-hydroxy-3-methylglutaryl-glycoside), an O -triglycosyl flavanone (narirutin 4′- O -glucoside) and a flavone O -glycosides (chrysoeriol 7- O -neoesperidoside). Moreover, the influence of the identified C - and O -glycosyl flavonoids on the antioxidant and acetylcholinesterase activity of these juices has been evaluated.